Analisa pertumbuhan balita berdasarkan berat badan, tinggi badan dan umur di posyandu - Fitria Hayu Palupi; Gipfel Remedina (MEDIA ILMU KESEHATAN, 2021)
Background: Assessment of body weight based on age according to WHO with NCHS standards is using percentiles, while weight assessment based on age according to WHO with NCHS standards is using percentiles. Height measurements were used to assess nutritional improvement status. assessment in this way is very easy to do to assess growth disorders. Nutrition problems in toddlers can be monitored during posyandu activities, so that nutritional disorders in toddlers can be immediately handled properly.Objective: The research design used was a cross sectional design, with a total sample of 99 children under five at the Posyandu in Kragilan Village.Methods: Data analysis used univariate analysis test with distribution and percentage results and used bivariate analysis using chi square test.Results: From the analysis with thetest chi square on BW / U, it was found that the value of P = 0.000 (<0.05) with the OR value at BW / U was 7.500 with a lower value of 1.768 and an upper value of 124.468, while the results of the analysis using thetest chi square on TB / U obtained a value P = 0.000 (<0.05) with the OR value at TB / U is 9,556 with a lower value of 1,198 and an upper value of 76,240.Conclusion: protein energy adequacy has a significant relationship on the indicator of body weight according to age and protein energy adequacy has a significant relationship on the indicator height according to age.